Implementation of Environmental Management Policy in Jagapati Village, Abiansemal District, Badung Regency - I Gusti Putu Suastina Putra; Gede Wirata; Ni Luh Putu Suastini (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Environmental management is a crucial component of achieving sustainable development, particularly in rural areas with the potential for environmental pollution due to livestock activities and household waste. One of the Provinsi Bali Government's efforts is through the implementation of Peraturan Daerah Provinsi Bali Nomor 1 Tahun 2017 concerning Environmental Protection and Management. However, in practice, various problems remain in Desa Jagapati, such as the direct discharge of livestock waste into rivers, the lack of waste treatment facilities, and low public awareness of environmental cleanliness. This study aims to determine why the implementation of environmental management policies in Desa Jagapati has not been effective and to identify strategies to improve them. The method used was descriptive qualitative, with data collection through observation, interviews, and documentation. The results indicate that the implementation of environmental management policies in Desa Jagapati has not been effective due to low public awareness, weak coordination, and minimal waste management. The main obstacles are a lack of outreach, limited resources, low commitment from implementers, and unclear standard operating procedures (SOP). Improvement strategies include education, the formation of environmental awareness groups, training, the provision of facilities, and a gradual and participatory work structure.